(untitled) (Conferencea, 2022)
The Ustyurt Plateau in north western Uzbekistan fauna of the family Reduviidae is summarized in this paper. In total, 7 genus and subgenus, and 15 species are listed from Uzbekistan (Karakalpakistan). two species, Reduvius ciliatus (Jakovlev, 1879) and Reduvius personatus (Linnaeus, 1758), is newly species from Uzbekistan.